Influence of the interaction between the inter- and intragranular magnetic responses in the analysis of the ac susceptibility of a granular FeSe0.5Te0.5 superconductor. (18th August 2015) - Mancusi, D; Polichetti, M; Cimberle, M R; Pace, S
Abstract: The temperature-dependent fundamental ac susceptibility of a granular superconductor in the absence of dc fields has been analyzed by developing a phenomenological model for effective magnetic fields, taking into account the influence of the magnetic interaction between the intergranular and the intragranular magnetizations due to demagnetizing effects. For this purpose a policrystal Fe-based superconductor FeSe0.5 Te0.5 sample has been studied. By the frequency dependence of the peaks of the temperature-dependent imaginary part of the fundamental complex susceptibility, the dependence on temperature of the characteristic times both for intergranular and intragranular relaxations of magnetic flux are derived, and the corresponding relaxation processes due to combinations of the flux creep, the flux flow and the thermally activated flux flow regimes are identified on the basis of the effective magnetic fields both at the sample surface and at the grains' surfaces. Such characteristic times, through the Havriliak–Negami function, determine the temperature and the frequency dependences of the complex susceptibility. The comparison of the numerically obtained curves with the experimental ones confirms the relevance, for identifying the intergranular and intragranular contributions to the ac magnetic response and the corresponding flux dynamical regimes, of the interaction between the intergranular and intragranular magnetizations due to demagnetizing effects.